(untitled) (Revista Educação, Artes e Inclusão, 2022)
The paper aims to provide a historical overview of the care of students with Visual Disabilities (VD) in the state of Acre, specifically in the city of Rio Branco, in the context of basic education and higher education by the Federal University of Acre (UFAC). For this, the advances and limitations on the theme of inclusive education and education in diversity are discussed, and at the end an overview of the achievements in the issue of the inclusion of VD in the school environment is presented, highlighting the need for the use of Assistive Technologies (AT) for these students. This is a qualitative research based on the analysis of documentary data and interviews. The results show the progress achieved in offering courses and pedagogical support for basic and higher education at UFAC in the context of VD in Rio Branco. In addition, there is a need to expand the services offered in the capital and in the interior of the state, and initial and continuing teacher training aimed at developing a sensitive view of differences.